Augmented Reality Based on Contextual Problem Scenarios on Problem Solving Ability and Cognitive Level of Elementary School Students - Sari Riski Wati; Singgih Bektiarso; Muhammad Irfan Hilmi; Aris Singgih Budiarso (Lembaga Bale Literasi, 2026)
This study examines the effect of Augmented Reality (AR) media based on contextual problem scenarios on students' problem-solving ability and cognitive learning levels in IPAS for Grade V elementary school students. The research was motivated by low problem-solving ability and suboptimal learning outcomes at Cluster 1, Sumberjambe District, Jember Regency, where a pre-assessment revealed a mean score of only 38.2 out of 100. AR media designed around contextual problem scenarios, specifically environmental pollution, was integrated within the Problem-Based Learning (PBL) model to visualize abstract concepts through interactive 3D objects using gyroscope-based markerless technology. A quasi-experimental design with a Non-Equivalent Control Group was employed. The research population consisted of all Grade V elementary school students in Cluster 1, Sumberjambe District, with a sample of 56 Grade V students selected from SDN Jambearum 01 (experimental class, n = 28) and SDN Pringgondani 01 (control class, n = 28). Data were collected using a problem-solving ability test based on Polya's four stages and an IPAS learning outcomes test covering cognitive levels C1–C4 of the revised Bloom's Taxonomy, analyzed using Independent Sample t-tests. The results showed a significant effect on problem-solving ability (t(54) = 9.177, p < 0.001), with the experimental class achieving a mean of 78.90 compared to 52.85 in the control class. A significant effect was also found on cognitive learning levels (t(54) = 4.968, p < 0.001), with the experimental class obtaining a mean of 83.21 versus 73.61. In conclusion, the use of AR media based on contextual problem scenarios effectively and significantly improves both problem-solving competency and cognitive learning levels in elementary school IPAS learning.